The Roman law of slavery : the condition of the slave in private law from Augustus to Justinian / William Warwick Buckland. - Buckland, W. W. (William Warwick), 1859-1946 (Cambridge library collection. Classics., 2010)
W. W. Buckland's highly regarded magisterial work of 1908 is a scholarly and thorough description of the principles of the Roman law with regard to slavery. Chapters systematically address, in Buckland's words, 'the most characteristic part of the most characteristic intellectual product of Rome'. In minute detail, Buckland surveys slaves and the complexity of the position of the slave in Roman law, describing how slaves are treated both as animals and as free men. He begins by outlining the definition of 'slave', their characteristics and conditions, giving examples of particular cases and describing for the reader the sorts of work a Roman slave might do. Carefully and comprehensively referenced throughout, this is a general survey of an important aspect of Roman law by a renowned Cambridge academic, which retains its status as an enduring classic.